VERNE HARRIS, Archives and Justice: A South African Perspective - Smith, Wendy (Archivaria, 2010)
Archives and Justice: A South African Perspective. VERNE HARRIS, with a foreword by Terry Cook. Chicago: Society of American Archivists, 2007. 476 p. ISBN 1-931666-18-0